Summer climate information recorded in tree-ring oxygen isotope chronologies from seven locations in the Republic of Korea - Choi, En-Bi; Park, Jun-Hui; Sano, Masaki; Nakatsuka, Takeshi; Seo, Jeong-Wook (Frontiers in Forests and Global Change, 2024)
The Republic of Korea is characterized by its north-to-south stretch and high mountain ranges along the eastern coast, resulting in terrain with higher elevation in the east and lower in the west. These geographical features typically lead to regional climate differences, either based on latitude or from east to west. In the present study, for effectiveness, the entire Korean peninsula was divided into four regions based on the geographical features: The Northeast Coast (NEC), Central Inland (MI), Southeast Coast (SEC), and South Coast (SC). Two test sites were chosen from each region, except for the SC. The linear relationship between the altitude of sites and the mean oxygen isotope ratio (δ18O) revealed a negative correlation; the highest (1,447 m a.s.l.) and the lowest altitude (86 m a.s.l.) sites had a mean δ18O of 27.03‰ and 29.67‰, respectively. The sites selected from the same region exhibited stronger correlation coefficients (0.75–0.79) and Glk (Gleichläufigkeit) (74–83%) between the tree-ring oxygen isotope chronologies (δ18OTR chronologies) than those from different regions (0.60–0.69/70–79%). However, subtle variations in pattern were observed in the comparison period during a few selected intervals (approximately 10 years). All the regional δ18OTR chronologies exhibited positive correlations with either June or July temperatures over Korea, whereas negative correlations with regional summer precipitation and SPEI-3. Moreover, the chronologies showed notable negative correlations with the water condition of western Japan. The findings of this study can be used as a scientific reference for the study of variations of rainfall in East Asia using δ18OTR chronology.